Wobec wyzwań globalnych. Uwagi o nauczaniu społecznym Benedykta XVI - RITTER, Cezary (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Caritas in Veritate, the third encyclical of Benedict XVI, which he signed in 2009, is simultaneously his first social encyclical. However, already in Deus caritas est of 2005, in particular in its second part, Benedict XVI addressed social issues by showing love (caritas) as as crucial an aspect of the mission of the Church as preaching the Word, prayer or the Sacraments. While the theme of the social teaching of the Church is justice realized in its social dimension, the motivation for the commitment to social justice is provided precisely by love conceived of as caritas. Owing to the inseparable bond between love and truth, love can be considered as genuine expression of humanity and an element of fundamental significance in interpersonal relations. The proper functioning of free market institutions involves general public confidence which results from the proper application of commutative and distributive justice. It is precisely a shortage of this kind of confidence that generates the present crisis. Economic activity requires that law be made by the legislative authority thus clearly facing a moral task, namely, to foster justice. Also, the right proportions should be preserved between the political authority, the market and the rank−and−file initiatives. The issue of justice, which, until not long ago, was a problem of particular societies or nations, has now become global. This in turn engenders the need to help goods from poor regions enter world markets, to ensure the due pay for their producers, Abstracts 353 and to assist the development of their professional skills and production technologies. Such is the necessary condition of the development of poor regions. Problems of this kind must be approached by means of immediate response to their particular manifestations, by proposing and applying solutions that will meet particular human needs. Nevertheless, in order to eliminate hunger in the world, to ensure peace and the stability of the planet, it is necessary to design a scheme of global dvelopment. This task results from the demand to foster the common good of the humanity. The moral responsibility of the human being in the spheres of technology and ecology is a significant aspect of sustainable development and it involves abandonment of the two extreme attitudes one may adopt in this respect: total lack of interference in the environment and abuse of this interference. The possibilities offered by modern biotechnology prompt the choice of one of the two categories of rationality: either of the one which opens the human reason to transcendence, or of that which confines the human reason to its immanence. In the face of the challenges the modern world poses, reason and faith must mutually support each other. It is important for the human being not to surrender to the technological mentality and to preserve the ability to respond freely to God’s calling. Translated by Dorota Chabrajska